Hypomorphic mutations in the larval photokinesis A, lphA, gene have stage-specific effects on visual system function in Drosophila melanogaster. - Gordesky-Gold, B.; Warrick, J.M.; Bixler, A.; Beasley, J.E.; Tompkins, L. (Genetics, 1995)
Of the many genes that are expressed in the visual system of Drosophila melanogaster adults, some affect larval vision. However, with the exception of one X-linked mutation, no genes that have larval-specific effects on visual system structure or function have previously been reported. We describe the isolation and characterization of two mutant alleles that define the larval photokinesis A (lphA) gene, one allele of which is associated with a P-element insertion at cytogenetic locus 8E1-10. Larvae that express lphA mutations are, like normal animals, negatively photokinetic, but they are less responsive to white light than lphA + controls. Larvae that are heterozygous in trans for a mutant lphA allele and a deficiency that uncovers the lphA locus are blind, which indicates that the mutant allele is hypomorphic. lphA larvae respond normally to odorants and taste stimuli. Moreover, the lphA mutations do not affect adult flies' fast phototaxis or visually driven aspects of male sexual behavior, and electroretinograms recorded from the compound eyes of lphA/deficiency heterozygotes and lphA1/lphA2 females are normal. These observations suggest that the lphA gene affects a larval-specific aspect of visual system function.